ADVANCED FOREIGN EXPERIENCE IN REGULATING LABOR MIGRATION IN UZBEKISTAN (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2025)
This article analyzes advanced foreign experiences in regulating labor migration in Uzbekistan. In particular, the successful practices of the Organization for Economic Cooperation and Development (OECD) countries in managing labor migration are studied and the possibilities of their application in the conditions of Uzbekistan are considered. The article analyzes the current state of labor migration, existing problems and future development prospects based on statistical data.